Iso-duration Determination of D′ and CS under Laboratory and Field Conditions - Triska, Christoph; Karsten, Bettina; Nimmerichter, Alfred; Tschan, Harald (International Journal of Sports Medicine, 2017)
Whilst Critical Speed (CS) has been successfully translated from the laboratory into the field, this translation is still outstanding for the related maximum running distance (D′). Using iso-duration exhaustive laboratory and field runs, this study investigated the potential interchangeable use of both parameters, D′ and CS. After an incremental exercise test, 10 male participants (age: 24.9±2.1 yrs; height: 180.8±5.8 cm; body mass: 75.3±8.6 kg; V̇ ˙VO2peak 52.9±3.1 mL∙min−1∙kg−1) performed 3 time-to-exhaustion runs on a treadmill followed by 3 exhaustive time-trial runs on a-400 m athletics outdoor track. Field time-trial durations were matched to their respective laboratory time-to-exhaustion runs. D′ and CS were calculated using the inverse-time model (speed=D′/t+CS). Laboratory and field values of D′ and CS were not significantly different (221±7 m vs. 225±72 m; P=0.73 and 3.75±0.36 m∙s−1 vs. 3.77±0.35 m∙s−1, P=0.68), and they were significantly correlated (r=0.86 and 0.94). The 95% LoA were ±75.5 m and ±0.24 m∙s−1 for D′ and CS, respectively. Applying iso-durations provides non-significant differences for D′ and CS and a significant correlation between conditions. This novel translation method can consequently be recommended to coaches and practitioners, however a questionable level of agreement indicates to use D′ with caution.